Uma metodologia sobre estratégias de gerenciamento de energia para usinas fotovoltaicas flutuantes instaladas sobre reservatórios de usinas hidrelétricas - Bruno Ude Todde Fonseca Valadares (2017)
This paper presents a methodology on hydric and energy management strategies for hydropower plants (HPP) combined with floating photovoltaic (PV) power plants. The combination of both power plants has technical advantages, such as the reduction of photovoltaic panel temperature, due to the cooling caused by proximity to water, and also commercial advantages, due to the savings caused by the non-use of land for the installation of the PV power plant. An economically attractive possibility is the connection of the photovoltaic power plant directly to an existing substation in the HPP, however, this alternative may not be possible by reasons of engineering limitations. In addition, it is important that the operational variables of the HPP be examined, for instance, reservoir characteristics, environmental conditions, and energy planning (short and long term). In long dry periods, for example, the electric energy from the PV panels can be used to power the Pumped Hydroelectric Energy Storage (PHES) system, aiming for the long-term generation availability, while at the same time smoothing the intermittent photovoltaic energy production. Aiming to deepen this discussion, this work presents a methodology to indicate which solution is the most indicated. The criteria used as reference is the fulfillment of the physical guarantee (PG) of the plant. As an example of application of this methodology, a case study was carried out for a hydroelectric power plant in operation. Environmental and operational conditions data were used on the mathematical models of the floating photovoltaic plant and the pumping system, in order to determine the additional energy generated and the level of the reservoir, for the alternatives of direct connection to the electric grid and the use of a PHES. A very discussed aspect in the literature refers to the decrease of the water evaporation from reservoir as a consequence of the surface covering by the floating panels, however, for the analyzed case, this effect was not representative. The two management strategies presented satisfactory achievements for the generation potential of the isolated HPP, where through the direct connection to the substation, the smallest simulated area (54.000m2) was able to double the percentage of permanence above PG. The second management strategy did not show the same success in terms of PG service for the evaluated HPP, but it presents itself as a promising solution in critical periods, such as those of water crisis, as well as offering an increase in generation potential, provides greater control capacity in meeting the long-term demands, and peak periods of energy demand. According to Brazilian Electric Sector (SEB) energy trading rules, both strategies presented commercial financial returns close to R$ 40.000.000,00 for the period analyzed (2010-2015).